THE UNDERLYING LINGUISTIC FACTORS AFFECTING GAMERS TO PLAY MOBILE LEGEND - Faiq Shabry; Dzul Fikri; Mutmainnah Mustofa; Sonny Elfiyanto (Graduate Program, University of Islam Malang, 2022)
This study aims to determine the daily activities of a student who likes to play games, the frequency, and the impact of playing these games in enriching the English vocabulary skills of students and general students. The general effects of playing onlinegames are commonly seen in negative terms, such as saying dirty words when they experience defeat or there an error in teamwork, so it can cause adverse effects on students. However, this study tries to uncover other impacts that are helpful in learning for students to understand English, especially in enriching their vocabulary skills. With this, researchers make observations to determine what essential things are needed to examine gamers who spends a lot of their daily activities playing games. Researchers also try to do activities that players do to get the same feel as felt by players. After making observations, the researchers conducted interviews. Based on the research results collected and processed, the results of this study indicate that students need curiosity to encourage them to enrich their English vocabulary collection. The results showed that they experienced a slight increase in vocabulary after playing Mobile Legend.